Syneresis, rheological characteristic and sensory consistency of the artichoke sauce (Cynara scolymus L.) - Mora Barandiarán, Francisco (2013)
The effect of the concentration of three hydrocolloids: CMC, guar gum and xanthan gum on the syneresis, rheological features and sensory consistency of the artichoke sauce (Cynara scolymus L.) Imperial Star variety was studied. The syneresis was determined by the water loss by centrifugation, the rheological features of the artichoke sauce was determined using a Brookfield RVDV – III model rheometer and finally, the sensory consistency was determined by measuring the degree of satisfaction with hedonic scale of nine points. A simplex lattice design blends with centroid expanded under the response surface methodology was applied to establish the effect of the concentration of hydrocolloid on syneresis, rheological features and sensory consistency. In all treatments, the apparent viscosity decreased with shear rate demonstrating a “non Newtonian” behavior of “general plastic” type with an “n” value less than 1 and an initial shear stress. The flow behavior index “n” was in the range of 0.0856 and 0.3131 (n < 1) and the consistency index “k” in the range of 84.55 y 167.80 Pa.sn , the initial shear stress was in the range of 9,10 y 13,51 Pa and consistency sensory presented score of “like” to “like slightly”. Finally, the hydrocolloid mixture was optimized over the area of feasible formulation. With the optimal mixture, corresponding to 0.28% CMC, 0.13% guar gum and 0.59% xanthan gum is expected to obtain a 0.089% of syneresis and a rating of 6 in terms of sensory consistency.